Artefacts of a fabricated past - Dunning, A (TORCH | The Oxford Research Centre in the Humanities, 2024)
The potential for forging the historical record has become far more evident in recent years, as powerful digital tools have made it easier to fabricate images and documents. This has made it more important than ever to preserve and study original historical artefacts, and to understand their full story. The Bodleian holds a number of objects that most observers would now describe as forgeries, but is every fake a lie?